PENGARUH LIKUIDITAS, PROFITABILITAS, SOLVABILITAS, DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN LQ45 - Virgin Ayu Fera Dahliawati; Yuli Kurniawati; Wulandari Harjanti (Media Akuntansi dan Perpajakan Indonesia, 2023)
The era of industrial revolution 4.0 drives the competition among companies to be more aggressive. Companies are competing to increase the valuation in order to draw investor’s attention. Based on that situation, a research is conducted aiming to examine whether or not liquidity, profitability, solvability, and dividend policy are influential toward the stock price in LQ45’s indexed company that is listed in Indonesian Stock Market (BEI). This research uses secondary data which is an annual report published in the official website of BEI. The sampling technique used is purposive sampling method which collects 105 companies for the last 3 years. The secondary data is measured using the ratio of CR, ROA, DER, and DPR which is then processed with SmartPLS software and analyzed using multiple linear regression by utilizing t test and F test to seek result based on the problem formulation. Results show that the significance value of probability is 0.009 meaning that profitability influences positively and significantly towards the stock price in LQ45 list of BEI. Meanwhile, the significance value of liquidity is 0.634, solvability is 0.417, and the dividend policy is 0.757 which means that liquidity, solvability, and dividend policy do not influence the LQ45 stock price in Indonesian Stock Market (BEI).